2019
DOI: 10.1002/arcp.1053
|View full text |Cite
|
Sign up to set email alerts
|

Consumers’ pursuit of material and experiential purchases: A review

Abstract: More than 15 years ago, Van Boven and Gilovich (Journal of Personality and Social Psychology, 85, 2003, 1193) presented evidence that experiential purchases make people happier than material purchases once consumers have covered their basic needs. This experiential advantage has attracted significant attention from researchers in the fields of social and consumer psychology. In this article, we review the literature on this subject. We first define the constructs of experiential and material purchases, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
90
0
10

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 101 publications
(104 citation statements)
references
References 97 publications
(154 reference statements)
4
90
0
10
Order By: Relevance
“…Across four studies, we found strong support for the idea that experiential gifts were construed as more significant moments and memories in consumers' autobiographical memory when thinking about the actual consumption of these gifts than their material counterparts. The main reason for this is because the consumption of experiential gifts is more meaningful to the self than the consumption of material gifts (Gilovich & Gallo, 2019). This result was consistent with a recent investigation that found consumers anticipate experiential purchase to represent unique opportunities that they cannot pass on (Bastos, 2019), yet our investigation proposes a more comprehensive construct of meaningful moments and memories as one important mechanism.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Across four studies, we found strong support for the idea that experiential gifts were construed as more significant moments and memories in consumers' autobiographical memory when thinking about the actual consumption of these gifts than their material counterparts. The main reason for this is because the consumption of experiential gifts is more meaningful to the self than the consumption of material gifts (Gilovich & Gallo, 2019). This result was consistent with a recent investigation that found consumers anticipate experiential purchase to represent unique opportunities that they cannot pass on (Bastos, 2019), yet our investigation proposes a more comprehensive construct of meaningful moments and memories as one important mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Consumption could involve material objects and experiences (Belk & Hsiu‐yen Yeh, 2011; Belk, 1988), a division closely relates to current terminology distinguishing experiential from material purchases, gifts, and consumption. Even though the distinction between experiential and material gifts and purchases is somewhat fuzzy (Gilovich & Gallo, 2019), it can be manipulated reliably in experiments, as shown in a recent meta‐analysis (Weingarten & Goodman, 2020). (3) Within these types of consumption, consumers are able to differentiate and appreciate different attributes in experiential and material types of consumption.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Consumers are experience seekers (Gilovich & Gallo, 2019), and we have no reason to believe that counterfeit buyers are different. Because experiences are lived rather than possessed, and because experiences make people happier than possessions (Van Boven & Gilovich, 2003), positioning luxury goods as experiences could deprive counterfeit buyers of the moments of pleasure, which genuine buyers live through.…”
Section: Towards a Research Agendamentioning
confidence: 99%